Transformaciones y continuidades en la gestión policial de conflictividades durante la pandemia - Goldin, Deborah Judith (2024)
This article presents the results of a research on the transformations in policing practices and population control during the COVID-19 pandemic, and the ways in which these changes were experienced by police officers in Córdoba (Argentina), in the case of the Villa María-Villa Nueva urban agglomerate during 2020-2021. Here we will address the conflicts that were relevant in this location during said period, analyzing the transformations that were identified in police practices and their ways of intervening in these conflicts. We analyze the interactions between police and citizens, looking to highlight the transformations of this already heterogeneous relation. Finally, we will inquire into the experiences of the police during the pandemic, with special emphasis on their perception of risk and recognition of their work, as well as on the use of force. On this basis, we consider that the pandemic strengthened the role of the police in population management, further highlighting the performance of a range of tasks unrelated to the prosecution of crime.